Myoblast and ADSC coculture on conductive highly aligned nanofiber scaffolds for human skeletal muscle tissue engineering - Shi, Xiu; Cai, Aijia; Arkudas, Andreas; Horch, Raymund E.; Jabeen, Sehrish; Schubert, Dirk W.; Weisbach, Volker; Kratzer, Simon; Stumpfe, Maximilian; Mengen, Lilly (Biomedical Materials, 2025)
Conductive materials play a crucial role in enhancing functional performance in muscle tissue engineering. This study investigates the impact of the conductive polymer polyaniline (PANi) in Polycaprolactone (PCL)-collagen Type I (PCL-collagen I) nanofiber scaffolds designed to support the coculture of human adipose-derived stem cells (ADSCs) and myoblasts (Mbs). The effect of varying PANi concentrations (0%, 2%, 4%, 6%) in PCL-collagen I nanofiber scaffolds was evaluated concerning the cell alignment, differentiation and gene expression of cocultured Mbs and ADSC. Nanofiber scaffolds with different PANi concentrations were analyzed. Acetic acid was used as a non-toxic and biocompatible solvent for electrospinning the nanofibers.In vitroexperiments involved a 1:1 coculture of Mbs and ADSCs for up to 28 d on the scaffolds. The cell viability, differentiation and myotube morphology were assessed using live-dead-assay, CCK-8-assay, immunofluorescence staining and gene expression analysis. Scaffolds with 2% and 4% PANi showed a higher percentage of live cells compared to the control at both 7 and 28 d. The nanofibers with 2%, 4% and 6% PANi concentration showed promising results in terms of cell differentiation and myotube morphology. After 14 d, the scaffolds with 4% PANi showed superior cell differentiation with strong myotube alignment along the nanofibers. At higher PANi concentrations (6%), only the myotube width increased significantly, whereas 4% PANi resulted in a markedly higher myotube number. PCL-collagen I nanofibers incorporating PANi enhance myoblast alignment and differentiation compared to the control group, showing promise for muscle tissue engineering applications. The non-toxic solvent makes the nanofibers suitable for translational purposes. Furtherin vivostudies are needed to explore the full impact on cellular function and regeneration.
CRIS-Team Scopus Importer:2025-12-12
Keywords: conductive nanofiber; muscle tissue engineering; myogenic differentiation; polyaniline (PANi)